2022
DOI: 10.1108/ijbpa-09-2021-0119
|View full text |Cite
|
Sign up to set email alerts
|

Urban solid waste challenges and opportunities to promote sustainable developing cities through the fourth industrial revolution technologies

Abstract: Purpose In less than a decade to Sustainable Development Goals, the urban solid waste (USW) emanating from households, especially in developing countries, calls for concern. Several policies have been suggested and some implemented, but the challenges facing USW management remain, especially in developing nations. Past studies demonstrated that the fourth industrial revolution (4IR) technologies can be used to improve urban public services. The role of 4IR in mitigating the challenges of USW is yet to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…Previous research, such as Ebekozien and Aigbavboa (2021), Bui and Tseng (2022) and Ebekozien et al. (2022b), confirmed that urban public services could use advanced digital technology.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Previous research, such as Ebekozien and Aigbavboa (2021), Bui and Tseng (2022) and Ebekozien et al. (2022b), confirmed that urban public services could use advanced digital technology.…”
Section: Introductionmentioning
confidence: 78%
“…Thus, the study adopted the framework. The phases are generation and separation; collection, transfer, transport; treatment; disposal; and recycling (Ebekozien et al. , 2022b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations